Ivacaftor pharmacokinetics and lymphatic transport after enteral administration in rats - Pozniak, Jiří; Ryšánek, Pavel; Smrčka, David; Kozlík, Petr; Křížek, Tomáš; Šmardová, Jaroslava; Nováková, Anežka; Das, Debanjan; Bobek, Daniel; Arora, Mahak; Hofmann, Jiří; Doušová, Tereza; et al. (Frontiers in Pharmacology, 2024)
Background: Ivacaftor is a modern drug used in the treatment of cystic fibrosis. It is highly lipophilic and exhibits a strong positive food effect. These characteristics can be potentially connected to a pronounced lymphatic transport after oral administration.Methods: A series of studies was conducted to describe ivacaftor basic pharmacokinetic parameters in jugular vein cannulated rats when dosed in two distinct formulations, an aqueous suspension and oil solution. Additionally, anesthetized mesenteric lymph duct cannulated rat model was applied to precisely assess the extent of lymphatic transport.Results: Mean±SD ivacaftor oral bioavailability was 18.4±3.2% and 16.2±7.8%, respectively, when administered as aqueous suspension and oil solution. The relative contribution of lymphatic transport to the overall bioavailability was 5.91±1.61% and 4.35±1.84%, respectively.Conclusions: Lymphatic transport plays only a minor role in the process of ivacaftor intestinal absorption and other factors are therefore responsible for its pronounced positive food effect.